IS SOMETHING WRONG WITH THE AYURVEDIC DRUGS ? - Robin-Victor Paul, (International Journal of Ayurveda and Pharma Research, 2017)
There is a common perception that "Ayurvedic" and â€œHerbalâ€ drugs are safe for human use. However, evidence in the literature proven time to time that these formulations are not safe for human consumptions due to toxicity associated with metals that are used in such preparations. Regulatory agencies need to step forward to actively regulate this industry and act proactively to preserve the trust and integrity of AYUSH system of medicines. Similarly, all stakeholders of AYUSH system of medicine have equal responsibility to dispel such misconceptions in people through their professional associations and gain public trust for their profession.